THE COMPARISON OF REFLECTIVITY INVERSION USING BASIS PURSUIT AND ORTHOGONAL MATCHING PURSUIT ON THIN-LAYER - DZIKRA FATAHILLAH (NIM: 12313009), AHMAD
The increasing demand of energy encourages oil and gas industry to conduct a reservoir exploration in thin-layer (thin-bed). Seismic method has an important role in oil and gas exploration but the limitation of frequency bandwidth would be one of the challenge of seismic section to resolve thin-layer resolution. Several studies have clearly shown there are several methods that have ability to resolve thin-layer resolution such as Basis Pursuit Inversion (BPI) while the process of BPI relatively takes a long running time to resolve the thin layers. Meanwhile, Orthogonal Matching Pursuit (OMP) method has the same ability as well as BPI within a shorter time periods. This study aims to analyze factors that affecting both BPI and OMP method, namely regularization parameter (lambda), noise, wavelet extraction and the length of dictionary matrices and to analyze the application of each factors to the methods. The result of synthetic data shows that wavelet extraction gave most impact on BPI result. BPI have tolerance to mis-phase within -14˚ until 14˚ on odd model and -16˚ until 16˚ on even model, and within -3 Hz until 3 Hz for mis-frequency on odd model. BPI can also give tolerance for convolutional noise within 40% on even model. Meanwhile OMP method has no resistance towards the alteration of wavelet extraction since OMP has no denoising factor so it is not optimal to be applied into real data. The validation of BPI methods on real data is conducted by comparing the correlation between BPIÃ‚Â’s result and well data. The result proved that BPI can resolve thin layer properly.